آثار الإفتاء الفضائي على المجتمع الإسلامي - طهراوي, الزبير (جامعة الوادي - University of Eloued, 2023)
يعالج هذا البحث موضوعا حساسا وخطيرا بتمثل في الفتوى الشرعية عبر الفضائيات، وقد حاولت في هذه الورقة البحثية تسليط الضوء على هذا النوع المستحدث من الإفتاء، فتطرقت في المبحث الأول إلى تعريف الإفتاء الفضائي لغة واصطلاحا وبيان أنواعه وخصائصه، أما المبحث الثاني فتطرقت فيه إلى تقييم الإفتاء الفضائي وآثاره على المجتمع بذكر إيجابياته وسلبياته ثم عرجت على حكم هذا الإفتاء وضوابط مشروعيته. ثم خاتمة سجلت فيها بعض النتائج والتوصيات. This research addresses a sensitive and dangerous topic represented in the fatwa of legitimacy through satellite channels, and i have tried in this paper to highlight this new type of fatwa, I touched in the first topic to the definition of space fatwa language and terminology and the statement of its types and characteristics, while the second topic touched on it To evaluate the space fatwa and its effects on society by mentioning its pros and cons, and then i dislike the ruling on this fatwa and the rules of its legitimacy. There was a conclusion in which some results and recommendations were recorded.
مقال
Keywords: الفتوى، الإفتاء الفضائي، القنوات الفضائية، المفتي، المستفتي; Fatwa; satellite; advisory ; satellite; channels; mufti; liquid